2023
DOI: 10.3390/nu15051074
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Micronutrient Deficiency in Adults: A Systematic Review and Meta-Analysis

Abstract: Food insecurity is a public health problem as it affects a wide array of individuals in the population. It can be characterized by food deprivation, lack of essential nutrition, lack of dietary education, lack of adequate storage conditions, poor absorption, and poor overall nutrition. The relationship between food insecurity and micronutrient deficiency requires more effort to deepen and discuss the relationship. This systematic review aimed to evaluate the association between food insecurity and micronutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Results of our study revealed an association between a lower diet quality and food insecurity. This finding aligns with previous studies that also identified a connection between food insecurity and diet quality(3638), extending to individuals following a gluten-free diet (24). The observation that only those experiencing very low food security exhibited a lower diet quality in this study, suggests that there may be a nuanced relationship between different levels of food security and diet quality, with very low food security having a more pronounced impact.…”
Section: Discussionsupporting
confidence: 92%
“…Results of our study revealed an association between a lower diet quality and food insecurity. This finding aligns with previous studies that also identified a connection between food insecurity and diet quality(3638), extending to individuals following a gluten-free diet (24). The observation that only those experiencing very low food security exhibited a lower diet quality in this study, suggests that there may be a nuanced relationship between different levels of food security and diet quality, with very low food security having a more pronounced impact.…”
Section: Discussionsupporting
confidence: 92%
“…While previous studies have not specifically highlighted the type of anemia, NDA is considered the most common cause 36 . Insufficient consumption of high‐quality food can increase the likelihood of developing micronutrient deficiencies, which in turn contribute to a higher risk of developing NDA 37–39 . NDA management typically includes dietary interventions and supplements, and most studies support the efficacy of these nonpharmaceutical interventions 10–12 .…”
Section: Discussionmentioning
confidence: 99%
“…36 Insufficient consumption of high-quality food can increase the likelihood of developing micronutrient deficiencies, which in turn contribute to a higher risk of developing NDA. [37][38][39] While these measures assisted in focusing our research on the objective, they may also have limited the broad applicability of our findings. Thus, our results may not be directly applicable to patients with more severe forms of the disease or those infected with different variants of the virus during various stages of the pandemic.…”
Section: F I G U R Ementioning
confidence: 99%
“…In Vietnam, MNDs have been reported to affect nearly 66% of children aged <5 years old, with 56%, 19%, 6% and 14% experiencing iron, zinc, vitamin A and vitamin D deficiencies, respectively (13). Both food insecurity (e.g., energy and nutrient inadequate diets) and micronutrient-poor, energy-dense diets are strongly associated with MNDs (14, 15). This co-occurrence has prompted the term “triple burden of malnutrition” (16).…”
Section: Introductionmentioning
confidence: 99%